Help seeking behavior in patients with alcohol dependence in a tertiary care hospital in eastern Nepal - Shakya, DR; Shyangwa, PM; Sen, BP (Journal of Psychiatrists’ Association of Nepal, 2014)
DOI: http://dx.doi.org/10.3126/jpan.v1i1.9922 Journal of Psychiatrists' Association of Nepal Vol.1(1) 2011: 15-19